Human Macrophages Clear the Biovar Microtus Strain of Yersinia pestis More Efficiently Than Murine Macrophages - Zhang, Qingwen; Xin, Youquan; Zhao, Haihong; Liu, Rongjiao; Xu, Xiaoqing; Yan, Yanfeng; Kong, Zhipeng; Wang, Tong; Qi, Zhizhen; Zhang, Qi; You, Yang; Song, Yajun; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
Yersinia pestis is the etiological agent of the notorious plague that has claimed millions of deaths in history. Of the four known Y. pestis biovars (Antiqua, Medievalis, Orientalis and Microtus), Microtus strains are unique in pathogenesis for being highly virulent in mice but avirulent in humans. Here, human peripheral lymphocytes were infected with the fully virulent 141 strain or the Microtus strain 201, and their transcriptomes were determined and compared. The most notable finding was that robust responses in the pathways for cytokine-cytokine receptor interaction, chemokine signaling pathway, Toll-like receptor signaling and Jak-STAT signaling were induced at 2 hours post infection (hpi) in the 201- but not the 141-infected lymphocytes, suggesting that human lymphocytes might be able to constrain infections caused by strain 201 but not 141. Consistent with the transcriptome results, much higher TNF- and IL-1 were present in the supernatants from the 201-infected lymphocytes, while inflammatory inhibitory IL-10 levels were higher in the 141-infected lymphocytes. The expressions of CSTD and SLC11A1, both of which are functional components of the lysosome, increased significantly in the 201-infected human macrophage-like U937 cells. Further assessment of the survival rate of the 201 bacilli in the U937 cells and murine macrophage RAW 264.7 cells revealed no viable bacteria in the U937 cells at 32 hpi.; however, about 5 to 10 % of the bacteria were still alive in the RAW264.7 cells. Our results indicate that human macrophages can clear the intracellular Y. pestis 201 bacilli more efficiently than murine macrophages, probably by interfering with critical host immune responses, and this could partially account for the host-specific pathogenicity of Y. pestis Microtus strains.